Andy Warhol - Vanitas 15.09.2024 - 16.03.2025 - Kloe, Fabian de 1982-; Jordens, Cynthia 1981-; Moore, Patrick 1962-; Morgan, Amber; Gray, Matt (nai010 publishers, 2024)
"Andy Warhol: Vanitas" explores Warhol’s preoccupation with temporality, spirituality and astrology. Warhol, a devoted Byzantine Catholic, regularly attended church, especially after his mother’s death in 1972 and following a near-fatal assassination attempt. - This book highlights a lesser-known part of his oeuvre, consisting of paintings and drawings of skulls and self-portraits, reminiscent of the seventeenth-century Vanitas genre. Spiritual subjects such as impermanence and time are explored through multimedia art and archival material from Warhol’s Time Capsules. To elaborate on the genre of Vanitas, the publication includes several original engravings and mezzotints by seventeenth-century Dutch engravers and painters from the collection of the Rijksmuseum in Amsterdam
Colophon: This publication is an initiative of SCHUNCK and was produced to accompany the exhibition "Andy Warhol: Vanitas" from September 15, 2024 to March 16, 2025, at SCHUNCK, Heerlen, The Netherlands
Keywords: Warhol, Andy -- 1928-1987; Vanitas; Ausstellungskatalog -- Schunck* -- 15.09.2024-16.03.2025 -- Heerlen; Aufsatzsammlung